MICRO-COSTING OF THE DIRECT LABOR OF PAID HOME CARE WORKERS: A SINGLE CASE STUDY - Cátia Correia Lima; Antônio Fernandes Costa Lima (Cogitare Enfermagem)
Objective: To calculate the average direct costs related to the labor of a paid home caregiver in carrying out the procedures that make up comprehensive care for a dependent elderly woman.